2009
DOI: 10.1593/tlo.08202
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenylethyl Ester and MG-132 Have Apoptotic and Antiproliferative Effects on Leukemic Cells But Not on Normal Mononuclear Cells

Abstract: Chemotherapy aims to limit proliferation and induce apoptotic cell death in tumor cells. Owing to blockade of signaling pathways involved in cell survival and proliferation, nuclear factor kappaB (NF-kappaB) inhibitors can induce apoptosis in a number of hematological malignancies. The efficacy of conventional chemotherapeutic drugs, such as vincristine (VCR) and doxorubicine (DOX), may be enhanced with combined therapy based on NF-kappaB modulation. In this study, we evaluated the effect of caffeic acid pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…In the present study, the effects of propolis extract Overall, our results indicate that propolis extracts had a strong and selective apoptotic effect on tumor cells that may be useful in future treatment of hematological neoplasias [30].…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, the effects of propolis extract Overall, our results indicate that propolis extracts had a strong and selective apoptotic effect on tumor cells that may be useful in future treatment of hematological neoplasias [30].…”
Section: Discussionsupporting
confidence: 62%
“…A PAS III flow cytometer (FC) (Partec, Germany) was used to acquire data, which were analyzed with the WinMDI 2.8 software (Scripps Institute, La Jolla, USA). For DNA fragmentation and the hypodiploid DNA content, cells were fixed with phosphate buffer saline (PBS) plus 2% p- formaldehyde (PFA) or 70% ethanol, respectively, stained with DAPI and evaluated by fluorescence microscopy (Olympus BX51, America Inc.) and FC (PAS III flow cytometer, Partec Germany), respectively 54,55 .…”
Section: Methodsmentioning
confidence: 99%
“…Caffeic acid has been reported to significantly inhibit the Akt signaling and caused an apoptotic cell death in PC‐3 human prostate cancer cells, TW2.6, and HCT 15 colon cancer cell lines . Tseng et al demonstrated that caffeic acid at the dose of 50 μM induces apoptosis via fragmentation of DNA and up‐regulation of p38MAPK and NGF/p75NTR in C6 glioma cells.…”
Section: Effects On Apoptosismentioning
confidence: 99%